Guía Técnica del cultivo de pitahaya (Hylocereus megalanthus) en la región Amazonas - Vargas Gutiérrez, Kryss Aracely; López Montañez, Ruth Noemí (Instituto Nacional de Innovación Agraria - INIA, 2020)
33 Páginas